Fixed point Theorems for Non-self mappings with nonlinear contractive condition in strictly convex FCM-spaces - Mohammad H.M. Rashid (Journal of the Indonesian Mathematical Society, 2020)
In this paper we define convex, strict convex and normal structures for sets in fuzzy cone metric spaces. Also, existence and uniqueness of a fixed point for non-self mappings with nonlinear contractive condition will be proved, using the notion of strictly convex structure. Moreover, we give some examples illustrate our results.